Fruit illumination stimulates cell division but has no detectable effect on fruit size in tomato (Solanum lycopersicum). Issue 1 (29th October 2014) - Okello, Robert C.O.; Heuvelink, Ep; de Visser, Pieter H.B.; Lammers, Michiel; de Maagd, Ruud A.; Marcelis, Leo F.M.; Struik, Paul C.
<x xml:space="preserve">Abstract</x> Light affects plant growth through assimilate availability and signals regulating development. The effects of light on growth of tomato fruit were studied using cuvettes with light‐emitting diodes providing white, red or blue light to individual tomato trusses for different periods during daytime. Hypotheses tested were as follows: (1) light‐grown fruits have stronger assimilate sinks than dark‐grown fruits, and (2) responses depend on light treatment provided, and fruit development stage. Seven light treatments [dark, 12‐h white, 24‐h white, 24‐h red and 24‐h blue light, dark in the first 24 days after anthesis (DAA) followed by 24‐h white light until breaker stage, and its reverse] were applied. Observations were made between anthesis and breaker stage at fruit, cell and gene levels. Fruit size and carbohydrate content did not respond to light treatments while cell division was strongly stimulated at the expense of cell expansion by light. The effects of light on cell number and volume were independent of the combination of light color and intensity. Increased cell division and decreased cell volume when fruits were grown in the presence of light were not clearly corroborated by the expression pattern of promoters and inhibitors of cell division and expansion analyzed in this study, implying a strong effect of posttranscriptional regulation. Results suggest the existence of a complex homeostatic regulatory system for fruit growth in which reduced cell division is compensated by enhanced cell expansion.